Quality of the surface water of a basin affected by the expansion of the agricultural frontier over the native forest in the Argentine Espinal region - Van Opstal, Natalia Veronica (2022)
Land use changes have led to the degradation of multiple ecosystem services and affected the quality of aquatic ecosystems. The aims of this study were (i) to assess the expansion of the agricultural border over the native forest of an Argentinean stream basin and (ii) to characterize the surface water quality, considering physicochemical parameters, and pesticide concentrations. The agricultural frontier expansion was estimated through the analysis of satellite image coverage. Samples of surface water were taken bimonthly for 2 years. The native forest cover decreased from 72% in 1987 to 60% in 2017 due to the sustained increase in agricultural activities. In surface water, the concentrations of cations decreased: Na > Ca > K > Mg, whereas those of anions decreased: HCO3 >  > Cl > SO4 > PO4. The 84 surface water samples analyzed revealed 25 pesticides, including herbicides (44%), insecticides (28%), and fungicides (28%). Herbicides were detected in more than 60% of the samples. 2,4-D, atrazine, cyproconazole, diazinon, glyphosate, AMPA, and metolachlor were detected in all the study sites and sometimes, 2,4-D, atrazine, dicamba, and metolachlor concentrations exceeded the guideline levels. The high sampling frequency of this study and the two annual cycles of crops in the basin enabled sensing of pesticide molecules and concentrations that had not been previously detected, indicating diffuse contamination. These findings signal an emergent challenge on the Espinal agro-ecosystem integrity due to changes in land use.